Analysis of Similarity/Dissimilarity of DNA Sequences Based on Chaos Game Representation - Wei Deng; Yihui Luan (Abstract and Applied Analysis)
The Chaos Game is an algorithm that can allow one to produce pictures of fractal structures. Considering that the four bases A, G, C, and T of DNA sequences can be divided into three classes according to their chemical structure, we propose different kinds of CGR-walk sequences. Based on CGR coordinates of random sequences, we introduce some invariants for the DNA primary sequences. As an application, we can make the examination of similarity/dissimilarity among the first exon of β-globin gene of different species. The results indicate that our method is efficient and can get more biological information.